1986
DOI: 10.1093/mutage/1.6.419
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in mutagenicity testing. II. Sister-chromatid exchange and micronucleus induction in rats, mice and Chinese hamsters treated with cyclophosphamide

Abstract: Comparative investigations of sister-chromatid exchange (SCE) and micronucleus induction in the bone marrow of rats, mice and Chinese hamsters with the cytostatic alkylating mutagen cyclophosphamide (CP) revealed remarkable species differences in their mutagenic responses. With both test systems the sensitivities of the three species can be ranked into the order rat greater than mouse greater than Chinese hamster. More explicit results were obtained with the SCE test than with the micronucleus test within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The difference in the dose required to evoke significant changes in behaviour and bladder inflammation in mice (present study) compared to rats (Lantéri-Minet et al, 1995) may be explained by differences in the metabolism of cyclophosphamide, in the pharmacokinetics of the parent compound or of the toxic metabolites, or in the sensitivity of the bladder to the toxins. The metabolism of cyclophosphamide appears to be very similar in all species (Madle et al, 1986). The pharmacokinetics of the parent compound, and the tissue distribution of the toxic metabolities vary somewhat between species, and even between different strains of mice (Madle et al, 1986;Kanekal et al, 1992), which may contribute to the higher dose required to produce significant effects in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the dose required to evoke significant changes in behaviour and bladder inflammation in mice (present study) compared to rats (Lantéri-Minet et al, 1995) may be explained by differences in the metabolism of cyclophosphamide, in the pharmacokinetics of the parent compound or of the toxic metabolites, or in the sensitivity of the bladder to the toxins. The metabolism of cyclophosphamide appears to be very similar in all species (Madle et al, 1986). The pharmacokinetics of the parent compound, and the tissue distribution of the toxic metabolities vary somewhat between species, and even between different strains of mice (Madle et al, 1986;Kanekal et al, 1992), which may contribute to the higher dose required to produce significant effects in mice.…”
Section: Discussionmentioning
confidence: 99%
“…MMC is well known to induce micronuclei in polychromatic erythrocytes in various mouse strains [4,[11][12][13]. CP is a mutagen in the chromosome aberration test, in the sister chromatid exchange and micronucleus test in vivo and in vitro [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing SCE frequencies and incidence of chromosomal aberrations, as well as yield of micronuclei, it was observed that the values differed. This phenomen had already been described (Madle et al, 1986), and it is explained by different mechanisms in the formation of genetic alterations. There was no correlation between SCE frequency and duration of exposure during the heavy spraying period, but a good correlation between incidence of unstable chromosomal aberrations, especially micronuclei, and duration of exposure was found.…”
Section: Discussionmentioning
confidence: 82%